Measuring efficiency of teaching hospitals in Malaysia - Moshiri, H.; Aljunid, S.M.; Amin, R.M.; Dahlui, M.; Ibrahim, W.N. (2011)
This study uses Data Envelopment Analysis, constant return to scale, input oriented to examine technical efficiency among three teaching hospitals in Malaysia. Variables of this study categorized two output and input; Outputs of the study includes number of discharged inpatient and number of visited outpatient by each department. Inputs of this study include bed, doctor, nurse and nonmedical staff. Results show that 87.5 percent of the selected clinical departments are operated inefficiently.